The effect of green mergers and acquisitions on the green transformation of heavily polluting enterprises: empirical evidence from China - Ma, Jingmei; Li, Zhiqing; Guo, Zile (Data science and management, 2025)
Against the backdrop of increasingly prominent global environmental issues, heavily polluting enterprises (HPPs) urgently need to find a path to green transformation that achieves sustainable development and overcomes efficiency challenges. Based on data on mergers and acquisitions of HPPs from 2010 to 2023, this article explores the direct impact and mechanisms of green mergers and acquisitions (GMAs) on enterprises green transformation. Research findings are as follows: (1) GMAs significantly promote the green transformation of HPPs, a conclusion that is robust across various tests. (2) Internal control and green innovation quality serve as partial and chain mediators, respectively, in the relationship between GMAs and the green transformation of HPPs. (3) Media pressure negatively affects the impact of GMAs on internal control. (4) The heterogeneity analysis shows that the GMAs of enterprises in the eastern region, non-state-owned enterprises, large enterprises, and enterprises in the electricity, heat, gas, and water production and supply industries have a more obvious impact on green transformation. These findings elucidate the mechanisms through which GMAs drive the green transformation of HPPs and offer empirical insights into supporting the sustainable development of such enterprises in China.